HUMANIZING AND LIBERZATION OF EDUCATION IN NOOSPHERE TO THINKING PARADIGM - Maria F. Solovyova (Открытое образование (Москва))
A concept of human potential is considered as one of main resources of development of country. Priority of humanity/pls is shown for cardinal reorganization of economy. At the level of administrative activity and motivation personalities are distinguished pedagogical, research, project and communicative groups of humanitarian competenses. Efficiency of noosphere paradigm of education is shown in bridging gap between the requests of companies and state for the competenses of specialist and citizen, qualificatory rates of technological development.